Overcoming the Challenges of Masturbation among Students of Tertiary Institutions in Nigeria through Sex Education and Educational Leadership - Innocent Joshua Chiawa Igbokwe (SIASAT, 2021)
Masturbation is assuming an exponential increase in proportion among students of tertiary institutions in Nigeria. The challenges of masturbation appear to be the most important and commonest sexual threat among students today. Sex education and educational leadership remain veritable interventionist approach to dealing with the challenges of masturbation among students. Unfortunately, sex education in this part of the world is uncoordinated or worse still, neglected while educational leadership seems to be a fantasy that ends in the classroom. This study examines the challenges of masturbation prevalent in tertiary institutions among students and thus, identifies the strategies of social intervention through sex education and educational leadership.